2021
DOI: 10.3390/ijms22105407
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Review of the Structural Features of Pentatricopeptide Repeats: Strategic Amino Acids, Repeat Arrangements and Superhelical Architecture

Abstract: Tricopeptide repeats are common in natural proteins, and are exemplified by 34- and 35-residue repeats, known respectively as tetratricopeptide repeats (TPRs) and pentatricopeptide repeats (PPRs). In both classes, each repeat unit forms an antiparallel bihelical structure, so that multiple such units in a polypeptide are arranged in a parallel fashion. The primary structures of the motifs are nonidentical, but amino acids of similar properties occur in strategic positions. The focus of the present work was on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Barik [ 2 ] offered a detailed analytical and comparative review of a special kind of protein motif, found as repeats that are commonly 34- and 35-amino acid residues long, and are known, respectively, as tetratricopeptide (TPRs) and pentatricopeptide repeats (PPRs). Both repeats are common in natural proteins, PPRs being particularly abundant in plants.…”
mentioning
confidence: 99%
“…Barik [ 2 ] offered a detailed analytical and comparative review of a special kind of protein motif, found as repeats that are commonly 34- and 35-amino acid residues long, and are known, respectively, as tetratricopeptide (TPRs) and pentatricopeptide repeats (PPRs). Both repeats are common in natural proteins, PPRs being particularly abundant in plants.…”
mentioning
confidence: 99%